Integrasi Al-Qur’an Dan Psikologi: Sebuah Pendekatan Holistik Dalam Ilmu Jiwa - Riyandi Baehaqi; Yasin Fahmi (Tamadduna: Jurnal Peradaban, 2025)
This study examines how the Qur'an and modern psychology are integrated to create a holistic approach to psychology. The main focus of the study is a hermeneutic analysis of the concept of the soul (nafs) found in the Qur'an, including the levels of the nafs (Al-Nafs al-Ammārah bi al-Sū', Al-Nafs al-Lawwāmah, and Al-Nafs al-Mutma'innah), as well as the concept of fitrah. The results of the study indicate that the nafs is a complex entity with material and spiritual dimensions, and its development is closely related to purification. The concept of fitrah provides an optimistic basis for psychological therapy centered on the innate goodness of humans. Holistic methods such as muhasabah, dhikr, and tazkiyatun nafs are offered in Sufi psychology to achieve spiritual awareness and mental health. This integration creates a new conceptual framework that blends the spiritual perspective of the Qur'an with the findings of contemporary empirical psychology. This allows for a broader understanding of the soul and the development of more useful interventions.